Well-posedness for the Cahn-Hilliard Equation with Neumann Boundary Condition on the Half Space (Journal of Partial Differential Equations, 2020)
In this paper, we investigate the Cahn-Hilliard equation defined on the halfspace and subject to the Neumann boundary and initial condition. For given initialdata in some sobolev space, we prove the existence and analytic smoothing effect ofthe solution.
Keywords: Cahn-Hilliard equation; Neumann boundary condition; analyticity; half space.